2020
DOI: 10.1177/1403494820977969
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression symptoms during the first 21 months after giving birth

Abstract: Aims: The first year after childbirth involves a major transition for women, which can accentuate inadequacies and feelings of powerlessness, making them vulnerable to depression. The aim of this study was to investigate the prevalence and frequency of maternal postpartum depressive symptoms at different times after giving birth (0–21 months). Methods: Data were collected cross-sectionally using a web questionnaire containing the Edinburgh Postnatal Depression Scale (EPDS). A total of 888 mothers with children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
9
0
3
Order By: Relevance
“…The reduction of depression symptoms in this study may be due to treatment among women who were referred to a clinical psychologist. However, in a Swedish cross-sectional study including 888 mothers, Rosander et al (2020) reported a peak in the levels of depression symptoms (EPDS ≥ 12) at 9 and 18 months postpartum after observing a comparable decrease in EPDS scores from birth to 6 months postpartum [ 27 ]. This suggests the need for a proactive screening program for early identification, management and in addition to follow-up for relapse prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of depression symptoms in this study may be due to treatment among women who were referred to a clinical psychologist. However, in a Swedish cross-sectional study including 888 mothers, Rosander et al (2020) reported a peak in the levels of depression symptoms (EPDS ≥ 12) at 9 and 18 months postpartum after observing a comparable decrease in EPDS scores from birth to 6 months postpartum [ 27 ]. This suggests the need for a proactive screening program for early identification, management and in addition to follow-up for relapse prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review and meta-analysis of 13 studies, women with inadequate social support were 6.27 times more likely to develop postpartum depression compared to those who had adequate social support (POR = 6.27, 95% CI 4.83–8.13, I 2 = 0) [ 35 ]. Yamada et al [ 27 ] suggest that several sources of social support may have a differential impact on postpartum depression. Women with no social support from a partner but have social support from others (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Frågan är dock om det räcker och vad forskningen säger om tidpunkt. I en studie med 888 nyblivna mammor med barn upp till 21 månader (Rosander et al 2020) har vi bland annat undersökt depressionssymptom vid olika tidpunkter efter födsel. Resultatet visade att depressionssymptomen var som lägst då barnet var cirka två månader, det vill säga ungefär vid den tidpunkt då screening sker.…”
Section: Föräldradepressionunclassified
“…Sett till hur ledare för föräldragrupper upplever det så handlar det om att skapa trygghet--något som ger sammanhållning. I studien av Rosander et al (2020) som presenterades i Kapitel 4 lyftes "att skapa trygghet" fram som den aspekt som krävde mest erfarenhet och upplevdes som en svårighet eller utmaning. Sammanhållning å andra sidan lyftes fram som en belöning, något som gör att det är roligt att jobba med föräldragrupper att man upplever att man lyckas bidra till att skapa sammanhållning.…”
Section: Trygghet Och Tillitunclassified
See 1 more Smart Citation